The Sustainability Practices among Dairy Farmers: The Case of Johor - Nalini, Arumugam; Zainab, Mohd Karim; Boniface, Bonaventure (2016)
Sustainability concept in agriculture is becoming widespread throughout industries in many fields even in crop production, livestock production and etc. Sustainable in agriculture is believed can give present and future good benefit to the farmers and society. However, in dairy sector in Malaysia, the sustainability concepts and practices seems not fully aware by the farmers which result in low self- sufficiency level in milk production. The self-sufficiency level in Malaysia is merely 6% and this lead to the urgency of importing more milk from other countries such as Australia, Holland and others. This study attempts to describe the descriptive thoughts on sustainability among Malaysian dairy farmers as well as describing the socio economic characteristics of the dairy farmers which will be the indicator of adoption of sustainability practices among dairy farmers. The preliminary data was collected using questionnaires through conducting face to face interviews with 50 dairy farmers from Johor. The Likerttype scale was employed to determine the practices that adopted by the dairy farmers. The gathered data was analysed using SPSS. The findings indicated that the dairy farmers had a higher understanding about the farm sustainability aspect which gives the highest mean score of 4.41. The second highest mean score is the ecological aspect which is about 4.13. The mean score for economic aspect shows the mean score about 4.00. The social aspect of sustainability revealed the lowest mean score which was about 3.46. The results indicated that the farmers favour sustainable practice is farm sustainability system. Sustainability in dairy farming sector in Malaysia can be achieved if the three elements of sustainability which is environmental, economic and social aspect were implemented and adopted in this sector.